Monetary consequences of alternative fiscal policy rules - Jukka Railavo (Bank of Finland, 2004)
In this paper we analyse the monetary impact of alternative fiscal policy rules using the debt and deficit, both mentioned as measures of fiscal policy performance in the Stability and Growth Pact (SGP).We use a New Keynesian model, with endogenous labour supply, distortionary taxation and no private capital.The economy is hit by two fundamental shocks: demand and supply shocks, which are orthogonal to each other.Monetary policy is conducted by an independent central bank that will optimise.Under discretionary monetary policy the size of the inflation bias depends on the fiscal policy regime.Using the timeless perspetive approach to precommitment, output persistence increase compared to the discretionary case.The result holds with the alternative fiscal policy rules, and inflation and output persistence reflects the economic data.With the deficit rules, the autocorrelation of the tax rate is near unity irrespective of the monetary policy regime, and irrespective of the fiscal policy parameters and targets.
URN:NBN:fi:bof-20140807465
Keywords: E52; E31; E61; E62; 330; inflation; optimal monetary policy; fiscal policy; policy coordination